Effect of Combination of L-Arginine and L-Carnitine on Serum AGEs Level, Kidney and Endothelial Function in Patients with Chronic Heart Failure - Kuryata, Olexandr; Sirenko, Oksana; Zabida, Abdunaser (Journal of Nutritional Therapeutics, 2019)
The aim of the study to evaluate the effect of combination of L-Arginine with L-Carnitine on GFR, serum AGEs level and endothelial function in chronic heart failure (HF) patients with preserved ejection fraction (HFpEF). Materials and Methods: 35 patients with mean age 60,1 [56,7; 77,3] years with an established diagnosis of HFpEF were enrolled. The patients were randomly and blindly divided into 2 groups: first (1st) group pts were treated with a combination of L-Carnitine and L-Arginine in addition to standard treatment; 2nd group pts – with L-Arginine in addition to conventional treatment. Standard laboratory blood tests, lipid profile, glucose, renal and liver function tests, serum advanced glycation end-product (AGEs) level, echocardiographic examination, flow-mediated dilatation (FMD%) were performed for all patients baseline and after 10 days of treatment. The glomerular filtration rate (GFR) was estimated using the CKD-EPI formula. Results: Median level of AGEs was 1.72 [1.34; 1.93] mg/ml. The level of AGEs was correlated with age (R = 0.71, p<0.05), disease duration (R = 0.69, p<0.05). After 10 days of treatment with a combination of L-Carnitine with L-Arginine mean AGEs was decreased by 13.1% in comparison with L-Arginine treatment group (p=0.0003). After the treatment in 1st group mean AGEs was significantly lower in comparison with the 2nd group (p=0.004). Baseline median level of GFR was 81.2 [72,1; 86,2] ml/min and correlated with disease duration (R = 0.71, p<0.05), AGEs level (R = -0.73, p<0.05). The inclusion combination of L-arginine aspartate with L-Carnitine contributed to the significant increase of GFR level (p=0.003). The median FMD% level was 6.2 [4.4; 7.9] % and correlated with age (R=-0.61, p < 0.05), GFR (R=0.54, p < 0.05). After the 10 days it had been established significant increasing of FMD% level on 47.9 % in 1st group (p=0.0005), and on 29.3 % in 2nd group (p=0.003). Endothelial function normalizing was achieved in 10 (66 %) pts of 1st group and in 9 (45%) pts of 2nd group (p=0.002). Conclusion: The combination of L-Carnitine, and L-Arginine improves kidney, endothelial function and contributes to decreasing of AGEs level in pts with HFpEF.